2018
DOI: 10.1111/dom.13300
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of the duodenal‐jejunal bypass liner in obese patients with type 2 diabetes mellitus: A case control study

Abstract: This study provides the largest, so far, hypothesis-generating evidence for a putative positive risk/benefit ratio for treatment of obese patients with type 2 diabetes mellitus with the DJBL as an alternative treatment option for this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 29 publications
0
40
0
Order By: Relevance
“…Overall, 23 studies met the eligibility criteria from the screened and assessed full-text publications. Due to overlap, 6 publications were excluded, leaving 17 publications in the final analysis (11 for DJBL and 6 for PPBS) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Details are listed in the flow chart presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 23 studies met the eligibility criteria from the screened and assessed full-text publications. Due to overlap, 6 publications were excluded, leaving 17 publications in the final analysis (11 for DJBL and 6 for PPBS) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Details are listed in the flow chart presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Favourable weight loss outcomes and metabolic control are expected by creating a physical barrier between the mucosa of the upper small intestine and the ingested food. Longitudinal temporal data on efficacy is lacking, and published complication rates are controversial [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…It is held in place by a nitinol anchor, such that food passes through it without coming into contact with the small intestine, thereby mimicking the bypass part of Roux-en-Y bariatric surgery. [1][2][3] The endoscopic insertion and removal of EndoBarrier are day case procedures, performed in less than an hour under general anaesthesia. This form of reversible bariatric procedure has been shown to reduce weight and improve glycaemic control in people with diabetes and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…This form of reversible bariatric procedure has been shown to reduce weight and improve glycaemic control in people with diabetes and obesity. [2][3][4][5][6][7][8] As previously described in detail elsewhere, 8 we established in 2014 a National Health Service (NHS) service providing EndoBarrier treatment to people with long-standing poorly controlled type 2 diabetes and obesity which continued to be a problem despite all attempts to improve the situation with diet and lifestyle mea-sures as well as available diabetes medications. We treated 62 people with diabetes with EndoBarrier in this service.…”
Section: Introductionmentioning
confidence: 99%
“…Surgery was required in 8 patients, but no deaths were reported. Despite these risks, Laubner et al ( 70 ) showed possible positive risk-benefit ratio in favor of DJBL for T2DM treatment.…”
Section: Introductionmentioning
confidence: 99%